Ilahiyat, Nubuwat, Ruhaniyat, dan Sam'iyyat: Metode Pendidikan Tauhid dalam Keluarga - Murwat, Ruhullah Taqi (Didaktika Religia, 2015)
The paper highlights the urgency monotheism education in family that can be measured by looking at the basis, purposes, and functions. The basis of monotheism education in a family is Al Quran and Al Hadith. The materials of monotheism education in a family are of four sorts, namely Ilahiyat, Nubuwat, Ruhaniyat, and Sam'iyyat. The methods of monotheism education in a family are monotheism utterance, Modeling, habituation, advice and supervision. Monotheism education in a family occupies the most important position in a family as the foundation of education and other educational purpose. Monotheism education is the spirit of other education, but monotheism education requires the help of other educational materials to deliver the spirit and purpose of monotheism. Therefore, children will perform all the activities of life with a solid foundation of monotheism.